2013
DOI: 10.1161/strokeaha.112.680223
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Normal-Appearing White Matter Precede Development of White Matter Lesions

Abstract: Background and Purpose— It is unknown whether white matter lesions (WML) develop abruptly in previously normal brain areas, or whether tissue changes are already present before WML become apparent on MRI. We therefore investigated whether development of WML is preceded by quantifiable changes in normal-appearing white matter (NAWM). Methods— In 689 participants from the general population (mean age 67 years), we performed 2 MRI scans (including diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
197
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(212 citation statements)
references
References 26 publications
(36 reference statements)
8
197
0
Order By: Relevance
“…[3][4][5][23][24][25] There is a growing body of evidence, however, that clinically significant WM injury may exist that is subthreshold of T2 FLAIR detection and that represents a form of microstructural injury. 6,7,21 DTI-based techniques, which are predicated on the quantification of the randomness of water molecule diffusion, are informative on the microstructural integrity of WM. 9,26,27 With respect to NAWM, several studies have used a DTI-based approach to emphasize that the detection of microstructural injury of NAWM precedes the genesis of overt WMH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][23][24][25] There is a growing body of evidence, however, that clinically significant WM injury may exist that is subthreshold of T2 FLAIR detection and that represents a form of microstructural injury. 6,7,21 DTI-based techniques, which are predicated on the quantification of the randomness of water molecule diffusion, are informative on the microstructural integrity of WM. 9,26,27 With respect to NAWM, several studies have used a DTI-based approach to emphasize that the detection of microstructural injury of NAWM precedes the genesis of overt WMH.…”
Section: Resultsmentioning
confidence: 99%
“…9,26,27 With respect to NAWM, several studies have used a DTI-based approach to emphasize that the detection of microstructural injury of NAWM precedes the genesis of overt WMH. 6,28 A recent study of patients with mild ischemic stroke demonstrated that MD was the most sensitive metric for distinguishing WMH from NAWM and that the accumulation of interstitial fluid is involved in WMH pathogenesis. 17 Therefore, it is reasonable to assume that DTI-based anisotropy metrics of NAWM provide insights into WM composition and, as a result, are informative of functional connectivity and overall cognitive performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These contradictory data may be explained in two different ways. One option may be that in the brain of these subjects there are ''invisible'' ultrastructural changes in normal appearing white matter that precede the development of imaging-detected WMH [57]. Another possible explanation could be that, although identifiable in conventional imaging, the burden of cerebrovascular pathology must reach a threshold before clinical deficits become evident [14].…”
Section: Discussionmentioning
confidence: 99%
“…4 As an example, recent studies using diffusion tensor imaging show an association between SVD and microstructural changes within selected white matter tracts, 5,6 changes which have been linked to gait disturbances, 7 decreased performance on cognitive testing, 8 and may precede the development of white matter lesions detected using conventional sequences such as T2 or FLAIR. 9 Despite such advances, a systems-level understanding of how SVD contributes to cognitive dysfunction is missing.…”
mentioning
confidence: 99%